Stability of motor-nonmotor subtype in early-stage Parkinson’s disease - Xiao, Yi; Wei, Qianqian; Ou, Ruwei; Hou, Yanbing; Zhang, Lingyu; Liu, Kuncheng; Lin, Junyu; Yang, Tianmi; Jiang, Qirui; Shang, Huifang (Frontiers in Aging Neuroscience, 2022)
Abstract Background The different clinical characteristics and prognostic value of the motor-nonmotor subtype were established by previous studies. However, the consistency of the motor-nonmotor subtype was still unknown in patients with early-stage Parkinson's disease. The current study aimed to evaluate the consistency of the moto-nonmotor subtype during five years follow-up in a longitudinal cohort. Method Patients were classified into three subtypes (mild-motor predominant, intermediate, diffuse malignant; or tremor-dominant, indeterminate, postural instability and gait difficulty) according to the previously verified motor-nonmotor and motor subtyping methods at baseline and every year in the follow-up. The agreement between subtypes was examined using Cohen’s kappa and total agreement. The determinants of diffuse malignant subtype at the fifth year of visit were explored using logistic regression. Results A total of 421 patients were included in the current study. There was a fair agreement of motor-nonmotor subtype at the one-year visit of follow-up (κ = 0.30±0.09, total agreement, 60.6%) and the following years, compared to the baseline subtype. The motor-nonmotor subtype had a lower agreement between baseline and follow-up than that of the motor subtype. The baseline motor-nonmotor subtype was the determinant of diffuse malignant at the fifth year of visit. Conclusion Many patients changed their motor-nonmotor subtypes during the follow-up. More attention should be paid to the consistency of PD subtyping methods in the future.